Pharmacokinetic study of anti-tb drug para-aminosalicylic acid and its metabolites: a possible relationship with the development of toxicity - Adams, Kim (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.